PENGELOLAAN ARSIP BERBASIS DIGITAL DENGAN MENGGUNAKAN TANDA TANGAN ELEKTRONIK DAN IMPLEMENTASI APLIKASI ARSIP MENGGUNAKAN ARTERI - Muhammad Sholeh; Hartono - (DHARMA BAKTI, 2018)
The current archive management has been influenced by the development of information technology. Archives are not only stored in physical form but also stored in digital form. With this digital archive the process of retrieval can be quickly done. Application support greatly determines the effectiveness in the process of digitizing the archives. The process of digitizing the archive does not just store in the form of files like PDF but also stored, processed and search process using the application. With this archive application the storage process, search process and other processes are done with the application. One of the applications based on open source is Arteri. Arteries are web-based archival applications built in order to integrate archives electronically. The process of socializing the use of Arteri is done with the target participants are librarians who are members of librarian forums of Indonesian universities, especially the DI Yogyakarta. Socialization is packaged in the form of workshops and its outcome is the librarians understand how to use Arteri as an application to manage archives.